Negative Correlation between Circulating CD4+FOXP3+CD127− Regulatory T Cells and Subsequent Antibody Responses to Infant Measles Vaccine but Not Diphtheria–Tetanus–Pertussis Vaccine Implies a Regulatory Role - Ndure, Jorjoh; Noho-Konteh, Fatou; Adetifa, Jane U.; Cox, Momodou; Barker, Francis; Le, My Thanh; Sanyang, Lady C.; Drammeh, Adboulie; Whittle, Hilton C.; Clarke, Ed; Plebanski, Magdalena; Rowland-Jones, Sarah L.; et al. (Frontiers in Immunology, 2017)
Regulatory T cells (Tregs) play a key homeostatic role by suppressing immune responses. They have been targeted in mouse and human cancer studies to improve vaccine immunogenicity and tumour clearance. A number of commercially available drugs and experimental vaccine adjuvants have been shown to target Tregs. Infants have high numbers of Tregs and often have poor responses to vaccination, yet the role Tregs play in controlling vaccine immunogenicity has not been explored in this age group. Herein we explore the role of CD4+FOXP3+CD127- Tregs in controlling immunity in infant males and females to vaccination with diphtheria-tetanus-whole cell pertussis (DTP) and / or measles vaccine (MV). We find correlative evidence that circulating Tregs at the time of vaccination suppress antibody responses to MV but not DTP; and Tregs four weeks after DTP vaccination may suppress vaccine-specific cellular immunity. This opens the exciting possibility that Tregs may provide a future target for improved vaccine responses in early life, including reducing the number of doses of vaccine required. Such an approach would need to be safe and the benefits outweigh the risks, thus further research in this area is required.